2014
DOI: 10.1523/jneurosci.2600-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and Inhibition Compete to Control Spiking during Hippocampal Ripples: Intracellular Study in Behaving Mice

Abstract: High-frequency ripple oscillations, observed most prominently in the hippocampal CA1 pyramidal layer, are associated with memory consolidation. The cellular and network mechanisms underlying the generation of the rhythm and the recruitment of spikes from pyramidal neurons are still poorly understood. Using intracellular, sharp electrode recordings in freely moving, drug-free mice, we observed consistent large depolarizations in CA1 pyramidal cells during sharp wave ripples, which are associated with ripple fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
164
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(178 citation statements)
references
References 69 publications
14
164
0
Order By: Relevance
“…In addition, despite perpetual changes in afferent activity under in vivo conditions (Buzsaki, 1986(Buzsaki, , 1989(Buzsaki, , 2002(Buzsaki, , 2006Buzsaki et al, 1992;Csicsvari et al, 1999;English et al, 2014;Grosmark et al, 2012;Louie and Wilson, 2001;Mizuseki et al, 2011;Montgomery et al, 2008;Srikanth and Narayanan, 2015;Tononi and Cirelli, 2006;Wilson and McNaughton, 1994;Ylinen et al, 1995a), specific neuronal subtypes maintain distinct functional signatures, say in terms of their excitability or oscillatory or frequency selectivity measurements, that are different from other neuronal subtypes even in the same brain region Shepherd, 2002, 2005;Johnston, 2007, 2008;Pike et al, 2000;Spruston, 2008;Zemankovics et al, 2010). Further, synaptic peer-reviewed) is the author/funder.…”
Section: Dissociation Between Different Forms Of Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, despite perpetual changes in afferent activity under in vivo conditions (Buzsaki, 1986(Buzsaki, , 1989(Buzsaki, , 2002(Buzsaki, , 2006Buzsaki et al, 1992;Csicsvari et al, 1999;English et al, 2014;Grosmark et al, 2012;Louie and Wilson, 2001;Mizuseki et al, 2011;Montgomery et al, 2008;Srikanth and Narayanan, 2015;Tononi and Cirelli, 2006;Wilson and McNaughton, 1994;Ylinen et al, 1995a), specific neuronal subtypes maintain distinct functional signatures, say in terms of their excitability or oscillatory or frequency selectivity measurements, that are different from other neuronal subtypes even in the same brain region Shepherd, 2002, 2005;Johnston, 2007, 2008;Pike et al, 2000;Spruston, 2008;Zemankovics et al, 2010). Further, synaptic peer-reviewed) is the author/funder.…”
Section: Dissociation Between Different Forms Of Homeostasismentioning
confidence: 99%
“…For instance, they manifest strong oscillations in the theta frequency range (4-10 Hz) during exploratory behavior and during rapid eye moment (REM) sleep, and show characteristic sharp-wave ripple patterns during rest and non-REM sleep. These distinct activity patterns have been postulated to serve specific functions such as in the consolidation of memory and in neural encoding of space (Buzsaki, 1986(Buzsaki, , 1989(Buzsaki, , 2002(Buzsaki, , 2006(Buzsaki, , 2015Buzsaki and Moser, 2013;Colgin, 2013;English et al, 2014;Grosmark et al, 2012;Hartley et al, 2014;Lisman and Jensen, 2013;Mizuseki and Buzsaki, 2014;Montgomery et al, 2008;Moser et al, 2008;Moser et al, 2015;Tononi and Cirelli, 2006;Wilson and McNaughton, 1994;Ylinen et al, 1995a;Ylinen et al, 1995b).…”
Section: Degeneracy In the Generation And Regulation Of Local Field Pmentioning
confidence: 99%
“…The recordings could survive severe mechanical disturbances and remain stable for 20 min while rats explored their environment freely. Other groups have shown that sharp intracellular recordings could be obtained and maintained in freely moving birds (Long et al 2010;Hamaguchi et al 2014;Kosche et al 2015;Vallentin and Long 2015) and mice (English et al 2014;Schneider et al 2014) using a head-mountable linear microdrive. The first such recordings were made from bird premotor HVC neurons to measure the subthreshold membrane potential dynamics during singing, and the resulting recordings supported a synaptic chain-like mechanism for birdsong generation (Long et al 2010).…”
Section: Intracellular Recordings In Freely Moving Animalsmentioning
confidence: 99%
“…High-quality and long-duration recordings of both types have been obtained successfully. There is, at present, no indication of differences in overall success rates when considering the latest versions of the methods applied to the same brain region (e.g., hippocampal subregion CA1) of the same species (e.g., mice) (English et al 2014;Lee et al 2014), although differences might emerge with increased use. However, there are some technical differences inherent to each approach.…”
Section: Intracellular Recordings In Freely Moving Animalsmentioning
confidence: 99%
See 1 more Smart Citation